Going global? Transnationality, women/gender studies and lessons from the Caribbean - Trotz, Alissa (2007)
Offers tentative reflections on notions of the global that underlie the imperial divide between area studies and women/gender studies in a North American context. Highlights practices of exclusion via Eurocentric rendering of global sisterhood based on a putatively universal notion of 'woman', and efforts to 'go global' that reduce areas, and people from those areas, to gendered types.